Enhanced Coercivity of Low-Density Barium Hexaferrite Magnets from Paste-Injection Molding - Wannisa Thongsamrit; Pongsakorn Jantaratana; Thanida Charoensuk; Chitnarong Sirisathitkul (My University, 2022)
Ceramic–polymer paste-injection molding is demonstrated as a facile fabrication route for barium hexaferrite magnets. Interestingly, these low-density (1.90–2.35 g/cm3) magnets exhibit substantial coercivity of 3868–4002 Oe. When ceramic paste without polymeric additives is used, reduced coercivity and slightly increased magnetizations are obtained from a magnet with the density of 2.55 g/cm3. Their magnetizations are also higher than those obtained from compactions of sol–gel-derived powders. For compact magnets (3.46–3.77 g/cm3), the DI water addition results in a slightly higher magnetization but lower coercivity than dry-pressed magnets. Compactions into disk and bar magnets give rise to comparable magnetic properties. The morphological characterizations reveal smaller barium hexaferrite particles leading to larger coercivity, and the density and shape of magnets have a less pronounced effect.
Keywords: Molding (decorative); Barium; Relative density; Magnetic Properties and Synthesis of Ferrites